3D Printed Polyurethane Scaffolds for the Repair of Bone Defects - Cooke, Megan E.; Ramirez-GarciaLuna, Jose L.; Rangel-Berridi, Karla; Park, Hyeree; Nazhat, Showan N.; Weber, Michael H.; Henderson, Janet E.; Rosenzweig, Derek H. (Frontiers in Bioengineering and Biotechnology, 2020)
Critical-size bone defects are those that will not heal without intervention and can arise secondary to trauma, infection and surgical resection of tumours. Treatment options are currently limited to filling the defect with autologous bone, of which there is not always an abundant supply, or ceramic pastes that only allow for limited osteo-inductive and -conductive capacity. In this study we investigate the repair of bone defects using a 3D printed LayFomm scaffold. LayFomm is a polymer blend of polyvinyl alcohol (PVA) and polyurethane (PU). It can be printed using the most common method of 3D printing, fused deposition modelling, before being washed in water-based solutions to remove the PVA. This leaves a more compliant, micro-porous PU elastomer. In vitro analysis of dental pulp stem cells seeded onto macro-porous scaffolds showed their ability to adhere, proliferate and form mineralised matrix on the scaffold in the presence of osteogenic media. Subcutaneous implantation of LayFomm in a rat model showed the formation of a vascularised fibrous capsule, but without a chronic inflammatory response. Implantation into a mandibular defect showed significantly increased mineralised tissue production when compared to a currently approved bone putty. While their mechanical properties are insufficient for use in load-bearing defects, these findings are promising for the use of polyurethane scaffolds in craniofacial bone regeneration.